2022
DOI: 10.1002/ps.7321
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural weeds: the contribution of domesticated species to the origin and evolution of feral weeds

Abstract: Agricultural weeds descended from domesticated ancestors, directly from crops (endoferality) and/or from crop-wild hybridization (exoferality), may have evolutionary advantages by rapidly acquiring traits pre-adapted to agricultural habitats. Understanding the role of crops on the origin and evolution of agricultural weeds is essential to develop more effective weed management programs, minimize crop losses due to weeds, and accurately assess the risks of cultivated genes escaping. In this review, we first des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 193 publications
0
27
1
Order By: Relevance
“…Common garden studies using experimental early generation crop-weed hybrids can provide tentative predictions of the effects of hybridization on the dynamics of weed populations and the likelihood of crop allele introgression into weeds (Campbell et al, 2006;Mercer et al, 2006;Presotto et al, 2019). In contrast to the common assumption (based on previous results) that early generations of crop-wild/weed hybrids suffer a dramatic loss of fitness relative to their wild/weedy counterpart (Snow et al, 1998;Cummings et al, 2002;Mercer et al, 2006;Campbell and Snow, 2007;Sahoo et al, 2010;Hooftman et al, 2015), our results showed at least equal survival and vastly higher plant biomass and fecundity in the reciprocal crop-weed hybrids relative to their parents in both contrasting environments, which could facilitate the introgression of crop alleles into weedy populations and stimulate the evolution of weediness and invasiveness (Schierenbeck and Ellstrand, 2009;Vercellino et al, 2022). Similar results, i.e., higher fitness of crop-wild/weed hybrids than the parents, have been reported in other Brassicaceae species (Hauser et al, 2003;Campbell et al, 2006).…”
Section: Evolutionary Consequences Of Reciprocal Crop-weed Hybridizat...contrasting
confidence: 99%
See 3 more Smart Citations
“…Common garden studies using experimental early generation crop-weed hybrids can provide tentative predictions of the effects of hybridization on the dynamics of weed populations and the likelihood of crop allele introgression into weeds (Campbell et al, 2006;Mercer et al, 2006;Presotto et al, 2019). In contrast to the common assumption (based on previous results) that early generations of crop-wild/weed hybrids suffer a dramatic loss of fitness relative to their wild/weedy counterpart (Snow et al, 1998;Cummings et al, 2002;Mercer et al, 2006;Campbell and Snow, 2007;Sahoo et al, 2010;Hooftman et al, 2015), our results showed at least equal survival and vastly higher plant biomass and fecundity in the reciprocal crop-weed hybrids relative to their parents in both contrasting environments, which could facilitate the introgression of crop alleles into weedy populations and stimulate the evolution of weediness and invasiveness (Schierenbeck and Ellstrand, 2009;Vercellino et al, 2022). Similar results, i.e., higher fitness of crop-wild/weed hybrids than the parents, have been reported in other Brassicaceae species (Hauser et al, 2003;Campbell et al, 2006).…”
Section: Evolutionary Consequences Of Reciprocal Crop-weed Hybridizat...contrasting
confidence: 99%
“…Heterosis, defined as the superiority of hybrids relative to their parents, is expected to occur after admixture between divergent populations that experienced genetic bottlenecks (Hovick et al, 2012; van Kleunen et al, 2015). Feral radish populations from Argentina probably experienced strong genetic bottlenecks, first as result of the species domestication, followed by species introduction into Argentina, and then as result of the feralization process (Vercellino et al, 2022). However, if current cultivars and feral populations are divergent enough to explain heterosis effects observed in this study is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hybridization is increasingly recognized as an important evolutionary phenomenon that can influence the evolution of both weeds and invasives (Ellstrand et al, 2010(Ellstrand et al, , 2013Vercellino et al, 2023). When hybridization occurs, the hybrid lineages harbor alleles from both progenitors, and the process of introgression will depend on the fitness of the hybrids relative to their parents (Mercer et al, 2007;Presotto et al, 2019).…”
mentioning
confidence: 99%